Perception of innovation in tourism with regard to controversial types of travel: A study of Polish consumers - Godlewski, Grzegorz (Turyzm/Tourism, 2021)
The aim was to determine how tourism innovations, including controversial types of tourism, are perceived by consumers. The hypothesis adopted was that there would be statistically significant correlations between demographic variables, the respondents’ perception of innovations and their propensity to engage in non-normative behaviour during tourism trips. The study was conducted using the CAWI surveying technique by means of an online questionnaire (N = 407). The respondents had noticed significant changes in the tourism industry and the majority were in favour of those innovations. These mainly related to the development of tourist service infrastructure. The study found a statistically significant difference between male and female respondents with more males in favour of introducing controversial tourism offers to the market. Male respondents were also more likely to engage in deviant behaviour.